1978
DOI: 10.1111/j.1432-1033.1978.tb12144.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Antibodies against Ferredoxin, Ferredoxin‐NADP+ Reductase and Plastocyanin with Spinach Chloroplasts

Abstract: Purified antisera against ferredoxin, ferredoxin-NADP' reductase and plastocyanin agglutinated osmotically shocked and washed spinach chloroplasts, prepared accordins to \tandard procedures. The monomeric antibody (immunoglobulin G fraction) of the reductase antiserum agglutinated chloroplasts specifically and directly, indicating that protruding structures (for example, the coupling factor) do not act as steric hindrances as has been suggested.With ferredoxin antiserum, the presence of a pentameric antibody (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Three hypotheses have been put forward on the location of plastocyanin in the thylakoid membrane. Plastocyanin might be located in the inner half of thylakoid membrane [15,25], in the stromal side of thylakoid [10,26] or in the hydrophilic cleft in the membrane [11,12,32,33]. The substantial amount of plastocyanin released from galactolipase-treated bean chloroplasts (about 40% of all plastocyanin present in chloroplasts) seems to indicate that this pool of plastocyanin is probably located in the stromal side of thylakoid membrane and not accessible to galactolipase action.…”
Section: Discussionmentioning
confidence: 99%
“…Three hypotheses have been put forward on the location of plastocyanin in the thylakoid membrane. Plastocyanin might be located in the inner half of thylakoid membrane [15,25], in the stromal side of thylakoid [10,26] or in the hydrophilic cleft in the membrane [11,12,32,33]. The substantial amount of plastocyanin released from galactolipase-treated bean chloroplasts (about 40% of all plastocyanin present in chloroplasts) seems to indicate that this pool of plastocyanin is probably located in the stromal side of thylakoid membrane and not accessible to galactolipase action.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding FNR in cyanobacteria is longer at the N-temintis than the expected sequence correspond-ing to tbe amino acid sequence of the usual purified protein (Sehiuchter and Bryant 1992). In eukaryotes, FKR is a nuclear enzyme synthesized in the cytoplasm as a polypeptide with a transit sequence for transport into the chloroplast (Grossman et al 1982) where il is bound to the stromal side of the thylakoid membrane (Bohme 1978). Spinach FNR interacts with a membrane polypeptide of 17.5 kDa (Valiejos et al 1984), II forms a homodimer which is apparently stabilized by interaction with a 10-kDa polypeptide called connectein (Shin et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion has been challenged recently. In contrast to Hauska et al, Schmid et al [29] and Bohme [30] observed a partial inhibition of electron transport and agglutination of thylakoids by antibodies to plastocyanin. Based on the extent of labelling of plastocyanin by hydrophilic chemical probes, it was proposed that plastocyanin is located in a hydrophilic cleft of the thylakoid membrane, where it may not be reached by the large antibody molecules, but to which the probes have access Since under the experimental conditions of this study electron transport at the level of plastocyanin is apparently influenced by the ionic strength within the thylakoids, which can be changed by impermeant nonionic compounds, at least a major fraction of plastocyanin should be localized within the thylakoids behind an osmotic barrier.…”
Section: Implicationsfor the Location Of Plastocyaninmentioning
confidence: 77%